2009
DOI: 10.1074/jbc.m109.041939
|View full text |Cite
|
Sign up to set email alerts
|

A Lipid Profile Typifies the Beijing Strains of Mycobacterium tuberculosis

Abstract: The Mycobacterium tuberculosis Beijing strains are a family highly prevalent in Asia and have recently spread worldwide, causing a number of epidemics, suggesting that they express virulence factors not found in other M. tuberculosis strains. Accordingly, we looked for putative characteristic compounds by comparing the lipid profiles of several Beijing and non-Beijing strains. All the Beijing strains analyzed were found to synthesize structural variants of two well known characteristic lipids of the tubercle b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
37
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 33 publications
(71 reference statements)
1
37
0
Order By: Relevance
“…Interestingly, in an attempt to discover the reason for the increased virulence of Beijing stains compared to other M. tuberculosis strains, it was found that all the analyzed Beijing strains synthesized structural variants of two well-known characteristic lipids of the tubercle bacillus, namely, phthiocerol dimycocerosates (DIM) and phenolglycolipids (PGL) (46), which correlated with higher CFU values (47,48). It could be speculated that the cell wall of StarvM.tb has a specific immune-activating lipid composition.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in an attempt to discover the reason for the increased virulence of Beijing stains compared to other M. tuberculosis strains, it was found that all the analyzed Beijing strains synthesized structural variants of two well-known characteristic lipids of the tubercle bacillus, namely, phthiocerol dimycocerosates (DIM) and phenolglycolipids (PGL) (46), which correlated with higher CFU values (47,48). It could be speculated that the cell wall of StarvM.tb has a specific immune-activating lipid composition.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, our approach was to identify naturally successful strains of M. tuberculosis from the population of London, United Kingdom, and to use the knowledge from previous in vivo and ex vivo studies carried out with isogenic strains (39)(40)(41) to develop hypotheses on and confirm/discover VFs relevant to their biology. We focused on closely related isolates from the CAS spoligotype family to minimize the potential impact that genetic background variability has on VF-associated phenotypes (25,43). Based on 15-locus MIRU-VNTR typing, each isolate of interest was associ- The genes corresponding to SNPs of interest (i.e., unique to C72 but not seen in C6, C14, or C40) were investigated in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…2). We restricted our in silico analysis to all four CAS isolates (C6, C14, C72, and C40) to eliminate LSPs, RDs, and SNPs that define lineages and to reduce the impact that the genetic background might have on VF-associated (25,38,43) phenotypes. We first searched for the presence/absence of RD149 (Rv1573-Rv1584c), as its absence was previously associated with reduced intracellular growth of CAS strains in THP-1 cells (56).…”
Section: Tuberculosis Strain Selection Hypothesis M Tuberculosismentioning
confidence: 99%
See 2 more Smart Citations